Two SnRK2-Interacting Calcium Sensor Isoforms Negatively Regulate SnRK2 Activity by Different Mechanisms. Issue 2 (7th November 2019) - Tarnowski, Krzysztof; Klimecka, Maria; Ciesielski, Arkadiusz; Goch, Grażyna; Kulik, Anna; Fedak, Halina; Poznański, Jarosław; Lichocka, Małgorzata; Pierechod, Marcin; Engh, Richard A.; Dadlez, Michał; Dobrowolska, Grażyna; et al.
Abstract : Two isoforms of SnRK2-interacting calcium sensor are expressed in Arabidopsis;they differ in calcium binding properties, but both inhibit SnRK2s and subsequently fine tune abscisic acid signaling. Abstract: SNF1-related protein kinases 2 (SnRK2s) are key signaling elements regulating abscisic acid-dependent plant development and responses to environmental stresses. Our previous data showed that the SnRK2-interacting Calcium Sensor (SCS) inhibits SnRK2 activity. Use of alternative transcription start sites located within the Arabidopsis ( Arabidopsis thaliana ) AtSCS gene results in two in-frame transcripts and subsequently two proteins, that differ only by the sequence position of the N terminus. We previously described the longer AtSCS-A, and now describe the shorter AtSCS-B and compare the two isoforms. The two isoforms differ substantially in their expression profiles in plant organs and in response to environmental stresses, in their calcium binding properties, and in their conformational dynamics in the presence and absence of Ca 2+ . Only AtSCS-A has the features of a calcium sensor. Both forms inhibit SnRK2 activity, but while AtSCS-A requires calcium for inhibition, AtSCS-B does not. Analysis of Arabidopsis plants stably expressing 35S :: AtSCS - A - c - myc or 35S :: AtSCS - B - c - myc in the scs - 1 knockout mutant background revealed that, in planta, both forms are negative regulators of abscisic acid-induced SnRK2 activity and regulate plant resistance against water deficit. Moreover, the data highlight biochemical, biophysical, and functional properties of EF-hand–like motifs in plant proteins.